REFLEKS FONEM-FONEM PROTO MALAYO-POLYNESIAN (PMP) TERHADAP BAHASA REJANG (Proto Malayo-Polynesian (PMP) Phoneme Reflexes in Rejang Language) - Dwi Atmawati (SAWERIGADING, 2014)
This study discussed about the reflexes of Proto Malayo-Polynesian (PMP) phonemes in Rejang language.The reflexes of Proto Malayo-Polynesian phonemes (PMP) in Rejang language covered consonants, vowels, semivowels, and diphthongs. Description of the phonemes reflexes employed a top-down reconstruction method. Based on the data analysis, it proved that reflexes of Proto Malayo-Polynesian (PMP) phonemesin Rejang language covered:(1) vowel reflexes e.g. /*e//e/, /ê/, /o/, /êa/, /oa/, /ø/; /*i//i/, /e/, /ê/, /ea/, /êy/;/*u/ /u/, /ê/, /o/, /oa/, /êw/; (2) consonant reflexes e.g. /*b//b/, /o/; /*d//t/; /*D//d/, /ø/; /*g//g/; /h//ø/;/*j//g/, /k/, /t/; /*k//k/, /?/; /*l//l/, /ø/; /*m//m/, /ø/; /*n//n/, /ñ/; /*ñ//ñ/, /n/; /*ŋ//ŋ/, /ø/; /*p//p/;/*q//?/, /ø/; /*r//r/, /ø/; /*R//l/, /?/, /ø/; /*s//s/; /*S//ø/; /*t//t/, /ø/; /*T//t/; /*z//j/, /y/; /*Z//d/, /j/;(3) semivowel reflexes e.g. /*w//b/, /w/, /a/, /ø/; /*y//y/, /e/; (4) diphthong reflexes e.g /*aw//oa/ in Rejanglanguage.